KONSEP POLIGAMI DALAM ALQURAN: STUDI TAFSIR AL-MISBAH KARYA M. QURAISH SHIHAB - Siti Asiyah; Muhammad Irsad; Eka Prasetiawati; Ikhwanudin Ikhwanudin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This paper aims to understand the interpretation of the polygamy verse from the perspective of contemporary Indonesian interpreters represented by M.Quraish Shihab as a problem solving for the rampant practice of polygamy in society. The discourse of polygamy in Islamic thought is an interesting controversy discussed. As offered by M. Quraish Shihab in his interpretation that polygamy in Islamic teachings is permissible not as a recommendation or as a mandatory thing, even then on fair terms. The existence of differences in each argument has the same basis of the Qur'anic text, namely Surat an-Nisa 'verse 3. The practice of polygamy sometimes has an impact on family relations that are not harmonious and unfair, on this basis polygamy needs to be reviewed with other approaches. To limit the study in this paper, this research uses a qualitative approach by applying a thematic interpretation method to obtain a comprehensive understanding of polygamy in the Qur'an. Polygamy in al-Misbah's interpretation is said to be fair, just here is not only immaterial (love and affection) but justice in measured material is not only obeying lust. Abstrak Tulisan ini bertujuan memahami tafsir ayat poligami perspektif mufassir Indonesia kontemporer yang diwakili oleh M.Quraish Shihab sebagai problem solving atas maraknya praktek poligami di masyarakat. Wacana poligami dalam pemikiran Islam menjadi kontroversi yang menarik dibahas. Sebagaimana ditawarkan M. Quraish Shihab dalam tafsirnya bahwasanya poligami dalam ajaran Islam diperbolehkan bukan bersifat anjuran atau hal yang wajib, itupun dengan syarat adil. Adanya perbedaan setiap argumen mempunyai dasar yang sama dari teks al-Qur’an yaitu surat an-Nisa’ ayat 3. Praktik poligami terkadang berdampak pada hubungan keluarga yang tidak harmonis dan kurang adil, atas dasar ini poligami perlu dikaji ulang dengan pendekatan-pendekatan lain. Untuk membatasi kajian dalam tulisan ini maka, Penelitan ini menggunaan pendekatan kualitatif dengan menerapkan metode tafsir tematik (maudu>’i) untuk memperoleh pemahaman yang komprehensif tentang poligami dalam al-Qur’an. Poligami dalam tafsir al-Misbah dikatakan boleh dengan syarat adil, adil di sini bukan hanya bersifat immaterial (cinta dan kasih sayang) melainkan keadilan pada materi yang terukur bukan hanya menuruti hawa nafsu.